Very-low-density lipoprotein response element in the promoter region of the human plasminogen activator inhibitor-1 gene implicated in the impaired fibrinolysis of hypertriglyceridemia. - Eriksson, P; Nilsson, L; Karpe, F; Hamsten, A (1998)
Hypertriglyceridemia and impaired fibrinolytic function are linked to coronary heart disease and other atherothrombotic disorders. Triglyceride-rich lipoproteins may attenuate fibrinolysis by increasing the plasma levels of plasminogen activator inhibitor-1 (PAI-1). Furthermore, a common 4/5 guanosine (4G/5G) polymorphism in the promoter region of the PAI-1 gene has been indicated to influence plasma PAI-1 activity and to be involved in an allele-specific response to triglycerides. Herein we show by transfection assays that VLDLs induce transcription of the human PAI-1 promoter in endothelial cells. A VLDL response element (VLDLRE) is located to residues -672 to -657 in the promoter region by electromobility shift assay, methylation interference, and DNase I footprinting, and its activity is shown to be influenced by the common 4G/5G polymorphism located adjacent to and upstream of the binding site of a VLDL-inducible transcription factor. These findings may provide a molecular explanation to the link between VLDL and PAI-1 activity elevation in plasma and to the interaction between the 4G/5G polymorphism and plasma triglycerides.